Electrophysiologic findings in patients with COVID-19 and quadriparesia in the northwest of Iran, A case series study and literature review - Fariba Eslamian; Negar Taleschian-Tabrizi; Behzad Izadseresht; Seyyed Kazem Shakouri; Shakiba Gholian; Mohammad Rahbar (Babol University of Medical Sciences, 2021)
Background: As a global health pandemic, the novel severe acute respiratory syndrome-coronavirus 2 (SARS- CoV2) outbreak began in December 2019 which rapidly spread to more than 200 countries. Respiratory complications and fever are the most obvious symptoms. Sometimes the neurological features are superimposed on the main disease and complicate patientchr('39')s status. Case Presentation: We describe 6 patients with COVID-19 and concomitant quadriparesia who underwent electrodiagnosis using EMG/NCS and results indicated 3 axonal variants of Guillain-Barré syndrome (GBS), including; 2 cases AMAN (acute motor axonal neuropathy), 1 case AMSAN (acute motor and sensory axonal neuropathy), three myopathies, including one combination of CIN/CIM (critical illness neuropathy/critical illness myopathy), one CIM and one acute polymyositis in these cases. Conclusion: Early diagnosis of the neuromuscular disorders of coronavirus could help for correct planning in the treatment of COVID-19 patients. Since GBS and inflammatory myopathies have an autoimmune basis, the immunotherapies such as IVIG, steroids, plasma exchange and other novel treatments as hemoperfusion can promise better and faster recovery in respiratory function and neuromuscular activity among COVID-19 patients who have musculature paralysis concomitantly. However, all these treatments are challenging and further clinical trials should be done to confirm the efficacy and safety of mentioned therapies.